Caffeine Suppresses GABA Receptor-Mediated Current in Rat Primary Sensory Neurons Via Inhibition of Intracellular Phosphodiesterase - Yang, J.Y.; Yang, G.; Ren, J.; Zhao, J.; Li Sh. (Нейрофизиология, 2015)
In acutely isolated rat primary sensory neurons, the effects of caffeine on GABA receptormediated current (IGABA) were investigated using a whole-cell patch clamp technique. We found
that applications of GABA (10-1000 µM) induced inward currents in a concentration-dependent
manner; the currents manifested obvious desensitization. Pretreatment with caffeine (0.01-
100 µM) suppressed IGABA in a noncompetitive manner; caffeine shifted the concentration –
response curve for GABA downwards compared to the control. Theophylline showed a similar
and stronger inhibitory effect on IGABA. Isolated application of 1 µM diazepam enhanced
IGABA, while pretreatment with 10 µM caffeine and 1 µM diazepam suppressed this current.
Intracellular application of the protein kinase A inhibitor H-8 dramatically weakened the
inhibitory effect of caffeine on IGABA. Because primary afferent depolarization is related to
GABAA receptors, our results suggest that caffeine might antagonize presynaptic inhibitory
effects of primary afferents, probably via inhibition of intracellular phosphodiesterase. Досліджували впливи кофеїну на струми, опосередковані рецепторами ГАМК (IGABA), в гостроізольованих первинних нейронах щура; використовували методику петчклемп у конфігурації «ціла клітина». Аплікації ГАМК
(10–1000 мкМ) викликали струми вхідного напрямку, амплітуда котрих була залежною від концентрації; струми демонстрували яскраво виражену десенситизацію. Попередня обробка кофеїном (0.01–100 мкМ) призводила до
неконкурентного пригнічення IGABA. Вплив кофеїну зміщував вниз криву концентрація–відповідь для ГАМК порівняно з контролем. Теофілін демонстрував подібні й навіть
сильніші гальмівні впливи на IGABA. Ізольована аплікація 1
мкМ діазепаму посилювала IGABA, тоді як попередня обробка
10 мкМ кофеїну перед дією 1 мкМ діазепаму пригнічувала цей струм. Внутрішньоклітинна аплікація H-8 (інгібітору протеїнкінази А) дуже значно послаблювала гальмівний
вплив кофеїну на IGABA. Оскільки деполяризація терміналий первинних аферентів опосередковується рецепторами ГАМК, наші результати вказують на те, що кофеїн може
протистояти пресинаптичному гальмуванню первинних аферентів. Ефекти кофеїну опосередковуються гальмуванням
внутрішньоклітинної фосфодіестерази.